PEMANFAATAN DIGITAL MARKETING TERHADAP PENINGKATAN PENDAPATAN JASA BIDANG KECANTIKAN PADA MAHASISWA PROGRAM STUDI D4 KOSMETIK DAN PERAWATAN KECANTIKAN - Anjani, Yasinta Roro; Okatini Armandari, Mari; Supiani, Titin (Jurnal Socia Akademika, 2024)
The research aims to determine the role of digital marketing in increasing service income in the beauty sector in students of the D4 Cosmetics and Beauty Care Study Program using a qualitative research method with a descriptive study focus on the research object, namely the number of 10 students who work in the field of beauty services and utilize digital marketing to increase their income. Data collection uses observation, interviews, and documentation. Data analysis techniques are carried out by data reduction, data display, and conclusion verification. The results of the study show that the use of digital marketing has a significant impact on increasing service income in the beauty sector among students of the D4 Cosmetics and Beauty Care Study Program. By leveraging various social media platforms such as Instagram, Facebook, TikTok, and WhatsApp, students have managed to expand their market reach, increase visibility, and attract more customers. The digital marketing strategy includes creating attractive content, using online booking features, and presenting customer testimonials. The majority of interviewees reported a 25-100% increase in revenue after using digital marketing, which was largely due to consistency in content creation and active interaction on social media.